(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This article explores the linguistic and cultural challenges involved in translating jokes from English into Uzbek. Humor is closely connected with language structure, cultural background, social values, and national mentality, which makes joke translation a complex process. The study analyzes different types of jokes, including wordplay, idiomatic expressions, cultural references, and situational humor, and examines the difficulties translators face when transferring humorous effects from one language to another. Special attention is paid to the loss of meaning, cultural adaptation, equivalence, and the preservation of comic effect in translation. The research also discusses effective translation strategies that help maintain both the linguistic meaning and cultural essence of jokes. The findings show that successful joke translation requires not only linguistic competence but also deep intercultural understanding.